ANALISIS KONDISI HUTAN MANGROVE DAN POTENSI SERAPAN KARBON MENGGUNAKAN DATA SENTINEL-2 DI KABUPATEN PESAWARAN - Adirama, Alfian Zamsami; Permana, Rizki Dimas; Alfajrin, Achmad Chalid Afif; Dwiputra, Mohamad Ashari; Widiya, Nanda; Dakhi, Sakti Vincensius Sozanolo; Destina, Weni Fira (Lambung Mangkurat University-Indonesia, 2024)
Climate change and global warming continue to occur up to the present. One of the gases significantly influencing climate change is carbon dioxide (CO2). The increase in CO2 can be mitigated by capturing carbon from the atmosphere and storing it in biomass in a process known as carbon sequestration. Forests play a crucial role as a mitigator in reducing global warming and climate change, acting as both a carbon sink and absorber. Mangrove forests, in particular have a high capacity for carbon storage, approximately three times more than terrestrial forests. This research aims to (1) assess the health condition of the mangrove forests in Pesawaran Regency and (2) estimate the CO2 absorption produced by Pesawaran Regency. The study utilizes Sentinel-2 satellite imagery and field data collection. Sentinel-2 images undergo Normalized Difference Vegetation Index (NDVI) transformation. The research results indicate that the mangrove forests in Pesawaran Regency in 2023 are predominantly in good condition, covering an area of 562,31 hectares (99%), while 6,12 hectares (1%) are in a degraded condition. The CO2 absorption by the mangrove forests pesawaran regency is estimated to be 336.367,47 tons CO2 and 591,75 tons CO2/ha.